Managerial wealth, behavioural biases and corporate monitoring : impact on managerial risk taking and value creation in UK high-tech and low-tech acquisitions - Gao, Lin (Cranfield University, 2005)
While the traditional agency model assumes managerial risk aversion and underinvestment in high-risk opportunities, the behavioural agency model allows for risk seeking by managers leading possibly to over-risky investments. Corporate governance mechanisms through their disciplining roles can steer managers towards optimal risk and avoid value destruction from either risk-deficit or risk-excess on the part of their managers. None of the existing studies offer a complete picture of managerial risk taking by allowing for both managerial risk aversion and risk seeking. The painting of just such a picture is the primary focus of this thesis. This thesis aims to answer the following two research questions in the context of corporate acquisitions: 1. What are the factors that drive managers to undertake risky projects? 2. To what extent is firm performance related to the optimal or suboptimal risk level of an investment project? This thesis investigates 289 UK domestic high-tech acquisitions and 289 matching low-tech acquisitions over the period 1993-2000. High-tech acquisitions are argued to be riskier than low-tech acquisitions. This thesis documents that fixed compensation, annual bonus, and LTIP cash provide few incentives for managers to conduct risky acquisitions. It finds significant evidence that equity-based wealth (such as LTIP shares, stock options and managerial shareholdings) which links managers' wealth to firm stock performance, has a nonlinear incentive effect on managers' selection of acquisition risk. At a low level, it encourages managers to pursue risky acquisitions. However, at high levels it discourages managerial risk taking. This nonlinear effect is mainly contributed to by managerial shareholdings. No evidence is found that stock options make managers select riskier acquisitions. Strong evidence is found that a high level of managerial wealth, which induces managerial risk aversion, can weaken the incentive alignment effect of equitybased wealth. This thesis finds significant evidence that managerial behavioural biases (such as overconfidence, over-optimism, and hubris) boosted by good past performance, firm glamour ratings by the stock market and a flattering media profile induce managers to engage in risky high-tech acquisitions. Corporate monitors are generally ineffective in disciplining managers' selection of acquisition risk. Overall, this thesis concludes that what makes managers take risky acquisitions appears to be the internal factors, i. e., factors that work within managers' inner selves and give them more confidence that they can control risks. External factors such as corporate monitoring devices that try to control managerial behaviour, do not necessarily boost managers' confidence in their risk managing capabilities. Regarding post-acquisition performance, this thesis documents that UK hightech acquisitions in the 1990s do not bring any value to acquirer shareholders up to three years after acquisition completion. However, high-risk high-tech acquisitions do not necessarily destroy more shareholder value than low-risk low-tech acquisitions. Acquisitions that are identified as at 'optimal' risk level perform better than under-risk acquisitions. Indeed, more shareholder value is created in acquisitions that are over-risk than acquisitions that are either optimal-risk or under-risk. Therefore, this thesis suggests that many UK acquirer managers during the period over 1993-2000 have foregone valuable but high risk growth opportunities and destroyed shareholder value more by being excessively risk-averse rather than being adventurous in their risk choices.